2013
DOI: 10.1039/c3nr00676j
|View full text |Cite
|
Sign up to set email alerts
|

Nanofibrous patterns by direct electrospinning of nanofibers onto topographically structured non-conductive substrates

Abstract: Patterning of electrospun nanofibers has recently attracted much attention for its usefulness in a wide range of applications. This paper reports on the generation of spatially defined nanofibrous patterns by direct deposition of electrospun nanofibers onto a variety of insulating substrates. It was found that topographical features of different non-conducting substrates could be readily replicated by the electrospun nanofibers of interest. To elucidate the underlying mechanism of nanofiber patterning, we have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
52
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(53 citation statements)
references
References 28 publications
1
52
0
Order By: Relevance
“…channels formed by aligned nanofibers or micropatterned films) and chemical/biological agents (i.e., growth factors) facilitate cell adhesion and differentiation. [4][5][6][7][8][9][10][11][12] 2 Nanofibers, mostly produced by an electrospinning technique, show great potential for NGC applications, since they have small diameter, large surface-to-volume ratio, and a similar morphology to native extracellular matrices. 13 NGCs with well-controlled nanofiber alignment structure is highly desirable.…”
Section: Introductionmentioning
confidence: 99%
“…channels formed by aligned nanofibers or micropatterned films) and chemical/biological agents (i.e., growth factors) facilitate cell adhesion and differentiation. [4][5][6][7][8][9][10][11][12] 2 Nanofibers, mostly produced by an electrospinning technique, show great potential for NGC applications, since they have small diameter, large surface-to-volume ratio, and a similar morphology to native extracellular matrices. 13 NGCs with well-controlled nanofiber alignment structure is highly desirable.…”
Section: Introductionmentioning
confidence: 99%
“…Although it is possible to generate patterned architectures with the fixed ground electrodes, it is obvious from the optical images that the alignment of fibers in the patterns improved significantly when the electrodes' activation was switched from one location to another. This resulted in the concentration of electric field between the active electrodes . In addition, because of the altering potentials between adjacent electrodes in short duration, the charged fibers were forcibly driven from one location to another.…”
Section: Resultsmentioning
confidence: 99%
“…The phenomena might be explained with the electrostatic field patterns and strengths. When an insulating air gap is introduced between the collector electrodes, it modifies the pattern of external electrical field . It is reported that the electrical field strength is equally distributed among the present (active) electrodes and has higher magnitude toward them.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Zhao et al . have studied the influence of insulating templates on electrospun nanofibrous mats . The deposition of the fibers was found to depend on the opening size of the templates .…”
Section: Introductionmentioning
confidence: 96%
“…This approach has enabled nanofibers to be preferentially directed towards the protrusions of a conductive template since they possess higher charge density. Alternatively, patterned fibrous mats have also been fabricated using easily available non‐conductive templates and by placing a thin layer of non‐conductive material over a conductive and patterned surface …”
Section: Introductionmentioning
confidence: 99%